2019
DOI: 10.3390/polym11050876
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Entangled Polymer Diffusion in Melts and Nanocomposites: A Review

Abstract: This review concerns modeling studies of the fundamental problem of entangled (reptational) homopolymer diffusion in melts and nanocomposite materials in comparison to experiments. In polymer melts, the developed united atom and multibead spring models predict an exponent of the molecular weight dependence to the polymer diffusion very similar to experiments and the tube reptation model. There are rather unexplored parameters that can influence polymer diffusion such as polymer semiflexibility or polydispersit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 218 publications
(366 reference statements)
1
50
0
Order By: Relevance
“…The fundamental problem of entangled (reptational) homopolymer diffusion in melts and nanocomposite materials in comparison with experiments has been reviewed by Karatrantos et al [17]. Carbon nanotubes (CNT) with persistence lengths of the order of several microns are one of the most attractive nanomaterials due to their exceptional mechanical, thermal, and electrical properties.…”
Section: Polymer Nanocompositesmentioning
confidence: 99%
“…The fundamental problem of entangled (reptational) homopolymer diffusion in melts and nanocomposite materials in comparison with experiments has been reviewed by Karatrantos et al [17]. Carbon nanotubes (CNT) with persistence lengths of the order of several microns are one of the most attractive nanomaterials due to their exceptional mechanical, thermal, and electrical properties.…”
Section: Polymer Nanocompositesmentioning
confidence: 99%
“…As a result, an exceptional degree of dispersion of the silica in the polymer and high degree of order in both thin film and bulk forms was achieved [18]. For matrix-free model systems [34,35] it was observed that NPs diffuse similarly to a polymer solution [36][37][38], while chains diffuse faster than NPs [39]. Ionic interactions are also included in the case of ionomers in which the morphology and phase behavior depend on the electrostatic strength [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the polymer chains have a faster diffusion than NPs, thanks also to their relatively short length. For the Kremer-Grest model, entanglement effect start to be felt for chains of over 100 beads, 48 i.e. four times larger than our case.…”
Section: Please Cite This Article As Doi:101063/50004437mentioning
confidence: 49%